Phonological Memory and the Acquisition of Grammar in Child L2 Learners. Issue 2 (June 2015) - Verhagen, Josje; Leseman, Paul; Messer, Marielle
<x xml:space="preserve">Abstract</x> Previous studies show that second language (L2) learners with large phonological me‐mory spans outperform learners with smaller memory spans on tests of L2 grammar. The current study investigated the relationship between phonological memory and L2 grammar in more detail than has been done earlier. Specifically, we asked how phonological memory relates to specific L2 grammar skills, after controlling for L2 vocabulary, and using different phonological memory tasks. Participants were 36 Turkish child learners of Dutch and 34 Dutch first‐language (L1) children. All participants completed a Dutch narrative task to assess their production of subject–verb agreement, auxiliaries, and verb placement, and a Dutch vocabulary test. Phonological memory was measured through serial recall of Dutch words, high‐probability nonwords, and low‐probability nonwords. The results show weak correlations between phonological memory and grammar in the L1 group due to ceiling effects. For the L2 group, moderate to strong correlations between phonological memory and grammar were found. Regression analyses showed that word recall significantly predicted all three L2 grammar skills, above and beyond vocabulary. These findings indicate that the ability to temporarily store L2 material in phonological memory is important for L2 grammar learning, but that specifics of the memory tasks also play a role.